MIRA-seq for DNA methylation analysis of CpG islands - Jung, Marc (Epigenomics, 2015)
AIM: To develop a reliable method for whole genome analysis of DNA methylation. MATERIALS & METHODS: Genome-scale analysis of DNA methylation includes affinity-based approaches such as enrichment using methyl-CpG-binding proteins. One of these methods, the methylated-CpG island recovery assay (MIRA), is based on the high affinity of the MBD2b-MBD3L1 complex for CpG-methylated DNA. Here we provide a detailed description of MIRA and combine it with next generation sequencing platforms (MIRA-seq). RESULTS: We assessed the performance of MIRA-seq and compared the data with whole genome bisulfite sequencing. CONCLUSION: MIRA-seq is a reliable, genome-scale DNA methylation analysis platform for scoring DNA methylation differences at CpG-rich genomic regions. The method is not limited by primer or probe design and is cost effective.